Pre- and post-pandemic comparisons in cardiovascular markers: a population-based study - Mayssam Nehme; Maria Eugenia Zaballa; Serguei Rouzinov; Julien Lamour; Silvia Stringhini; Silvia Stringhini; Silvia Stringhini; Idris Guessous; Idris Guessous (Frontiers in Cardiovascular Medicine)
IntroductionThe COVID-19 pandemic, starting in 2020, raised concerns about potential long-term health impacts, including its effects on cardiovascular health and related biomarkers. This study part of the Bus Santé in Geneva, Switzerland, compared cardiovascular and metabolic profiles pre- (2016–2019) and post-pandemic (2023–2024) among individuals aged 30–75.MethodsParticipants completed questionnaires and underwent a clinical visit, including a physical examination and fasting blood test to assess lipid and glycemic profiles. Linear regression was used to estimate results including mean systolic and diastolic blood pressure, cholesterol, and glycemic profiles, after adjusting for age, sex, smoking, and socioeconomic status. Quantile regression models were used to estimate median values.ResultsA total of 4,558 participants were included. The study observed modest declines in mean glucose, cholesterol, HDL, and LDL levels post-pandemic, with stable blood pressure. The prevalence and treatment rates of diabetes, hypertension, and dyslipidemia remained consistent. Unawareness of these conditions was stable.ConclusionDespite initial fears of a pandemic-induced health debt, results indicate healthy cardiovascular profiles post-pandemic, likely driven by improved lifestyle behaviors. This study highlights the importance of monitoring of cardiovascular health and suggests that lifestyle improvements may offset potential adverse pandemic effects in developed nations like Switzerland.